PENGARUH KEPUASAN KERJA dan KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION PEGAWAI DINAS KOMUNIKASI dan INFORMATIKA KOTA BANDAR LAMPUNG - ansori uhamka; ansori uhamka (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
This research was conducted at the Office of Communication and Information Technology of Bandar Lampung City. This study aims to examine partially and simultaneously how the effect of Job Satisfaction, Organizational Itmen on Turnover Intention Staff of the Communication and Information Office of Bandar Lampung City. The type of research used in this study was quantitative research with associative methods. The sampling method in this study used Non Probability Sampling. The respondents in this study were 54 Employees. Document analysis tools used in this study were the analysis of Multiple Linear Regression and hypothesis testing using t test and F test. The research results of the researcher did partially produced that Job Satisfaction and Organizational Commitment to Turnover Intention Employees of the Communication and Informatics Office of Bandar Lampung City. And the results of simultaneous research that Job Satisfaction and Organizational Commitment to Turnover Intention Staff of the Communication and Information Office of Bandar Lampung. by the researcher, it is expected that the leadership of the Communication and Informatics Office of Bandar Lampung City can pay more attention to and improve the conditions and conditions of the employee's work environment, for example by paying more attention to the harmony between superiors and subordinates as well as among employees must be maintained properly, so that a positive working relationship can be established which of course can improve work morale and a sense of employee organization commitment, so that employees can improve effective and efficient performance.